PUBLIC OPINION FORMATION TOWARD THE FREE NUTRITIOUS MEALS PROGRAM ON SOCIAL MEDIA ‘X’: A STUDY DURING THE PRABOWO-GIBRAN ADMINISTRATION - Bilqis Rizki Vinaya; Astri Wulandari (RADJA PUBLIKA, 2025)
Public opinion encompasses the views, attitudes, and collective reactions of society toward an issue in the public sphere. In the digital era, social media facilitates rapid interaction and information exchange, enabling public opinion to form and spread quickly through online discussions. One of the most discussed public issues in Indonesia is the Free Nutritious Meals Program (MBG), launched during the Prabowo-Gibran administration. The program sparked significant attention and conversations, especially on the platform ‘X’. Although the policy was introduced with positive intentions, such as reducing malnutrition and supporting local farmers, it also raised concerns related to budget, implementation quality, and readiness. This study uses a descriptive quantitative method through an online survey to explore how the public perceives the MBG program on platform ‘X’. A total of 400 respondents were selected using purposive sampling. The questionnaire was based on Abelson’s public opinion theory, covering belief, attitude, and perception. The findings indicate that public opinion on platform ‘X’ leans toward cautious or passive disagreement. Most respondents recognize the good intentions behind the program but remain sceptical about its execution and long-term sustainability. Average scores for belief, attitude, and perception dimensions fall below the threshold of strong agreement. In conclusion, the MBG program is yet to gain widespread public trust on social media. Although not fully rejected, the program’s reception reflects ongoing critical evaluation and hesitant support from users, shaped by both its perceived shortcomings and the dynamic public discourse occurring online.